(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This paper explores the phenomena of code-switching and linguistic borrowing within multilingual societies, examining their intricate relationship with identity, culture, and communication. It discusses how speakers alternate between languages or dialects as both a linguistic strategy and a manifestation of social identity and group affiliation. The reasons for code-switching, such as clarity, identity expression, and maintaining conversational coherence, are explored in various contexts. Linguistic borrowing is presented as a complementary process where foreign vocabulary is integrated, reflecting cultural heritage and adaptation. The paper highlights how these linguistic practices shape and reflect individual and collective identities, particularly in diasporic communities, and how they navigate cultural dualities and social hierarchies. Furthermore, it addresses the cultural implications, showing how language use mirrors societal change and the negotiation of cultural identities in response to globalization and migration. While code-switching can enhance communication and foster intercultural understanding, potential challenges like misinterpretation and language inequality are also acknowledged. The study concludes by emphasizing the importance of understanding these dynamic linguistic interactions for promoting inclusiveness and respecting linguistic diversity in an evolving global landscape.